2013
DOI: 10.1128/cvi.00612-12
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Vaccine Displaying the Loop-Neutralizing Determinant from Protective Antigen Completely Protects Rabbits from Experimental Inhalation Anthrax

Abstract: We previously showed that a multiple antigenic peptide (MAP) vaccine displaying amino acids (aa) 304 to 319 from the 2␤2-2␤3 loop of protective antigen was capable of protecting rabbits from an aerosolized spore challenge with Bacillus anthracis Ames strain. Antibodies to this sequence, referred to as the loop-neutralizing determinant (LND), are highly potent at neutralizing lethal toxin yet are virtually absent in rabbit and human protective antigen (PA) antiserum. While the MAP vaccine was protective against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Recently advances in enhancement of the immune response through cofactors targeting TLR signaling have been reported as well (219). A new vaccine using recombinant PA has not yet been approved; however, several, including those utilizing mutant PA variants with less toxicity and higher immunogenicity, are in development or clinical trials (17,25,68,86,118,136,188,189,277).…”
Section: Vaccinesmentioning
confidence: 99%
“…Recently advances in enhancement of the immune response through cofactors targeting TLR signaling have been reported as well (219). A new vaccine using recombinant PA has not yet been approved; however, several, including those utilizing mutant PA variants with less toxicity and higher immunogenicity, are in development or clinical trials (17,25,68,86,118,136,188,189,277).…”
Section: Vaccinesmentioning
confidence: 99%
“…We have previously shown that immunization with epitope-focused immunogens using either research adjuvants like Freund's or AlOH-containing human-use adjuvants can elicit Ab specific for a linear determinant in the 2β2-2β3 loop of PA which can mediate protection of rabbits from aerosolized spore challenge with B. anthracis Ames strain [10-12]. This epitope, referred to as the loop neutralizing determinant (LND), appears to be a functionally critical target for Ab, as relatively low serum titers of LND-specific Ab are capable of protecting rabbits from high dose aerosol challenge.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that immunization with epitope-focused immunogens can elicit Ab specific for a linear determinant in the 2β2–2β3 loop of protective antigen (PA) which can mediate protection of rabbits from spore challenge with B. anthracis Ames strain [7,8]. This protective neutralizing epitope, referred to as the loop neutralizing determinant (LND), is found within a segment of PA critical to the translocation of edema and lethal factor into cells [911].…”
Section: Introductionmentioning
confidence: 99%